Hidrólise parcial da superfície do polyethylene terephthalate (PET): transformando um rejeito em um material de troca catiônica para aplicação ambiental Partial hydrolysis of pet surface: transforming a plastic waste into a material with cationic exchange properties for environmental application - Marcelo G. Rosmaninho (Química Nova, 2009)
In this work it is proposed a simple and versatile undergraduate chemical experiment in polymer and environmental technology based on the process of polyethylene terephthalate (PET) hydrolysis. Polyethylene terephthalate from post-consume bottles is submitted to a controlled partial hydrolysis which allows the students to follow the reaction by a simple procedure. The students can explore the reaction kinetics, the effect of catalysts and the exposed polyethylene terephthalate surface area on the hydrolysis reaction. The second and innovative part of this experiment is the technological and environmental application of the hydrolyzed polyethylene terephthalate as a material with cation exchange properties. The surface hydrolyzed polyethylene terephthalate can be used as adsorbent for cationic contaminants.